Planning for Migration of Export Materials into Finished products CPG (Consumer Packaged goods) - Trujillo Liñán, Laura; Meneses Trujillo, Roberto (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The production of materials can lead to unnecessary inventory in plants and reduce living space in the warehouse. It is for this reason that the objective of this research is an innovative proposal that has to do with an optimized process to reduce wasted materials in inventory. For this, a market investigation will be carried out to do analysis with average base data for changes in materials in finished products. In the end, our proposal will achieve better productivity levels, better calculations of lead time with the supplier and alignment with the plant, and greater visibility of materials in development.